The connected hippocampus - O'Mara, S. M. (Shane M.); Tsanov, Marian (Progress in brain research, 2015)
"A substantial body of data suggests that the hippocampal formation plays a critical role in the biological processes underlying at least some forms of memory. Sometimes, however, it feels when reading the many, many papers published annually on the hippocampus that it sits apart from the brain, with its functions analysed in a narrow hippocampo-centric framework--as if the purpose of the rest of the brain is to serve the information processing needs of the hippocampus! This point is made a little facetiously and exaggeratedly, of course. Nonetheless, we felt the need to assuage these feelings by assembling this volume to encourage researchers to situate the hippocampus as part of a network connected to the rest of the brain and not to consider it in isolation. We therefore present a selection of chapters that concentrate on understanding the functions of the hippocampus in terms of the connectivity of the hippocampus itself: in other words, in terms of its cortical and subcortical inputs and outputs"--Publisher's description